LAS CADENAS DE TELEVISIÓN ESPAÑOLAS FRENTE AL DEBATE DEL 13J: ESTRATEGIAS DE PROGRAMACIÓN Y AUDIENCIA SOCIAL - Marta SAAVEDRA LLAMAS,Leticia RODRÍGUEZ FERNÁNDEZ, (Fonseca, Journal of Communication, 2023)
The television debate represents a decisive factor in political communication campaigns, and even more so if we consider that the television channels arbitrate social audience strategies that cause the message to be transmedia. The candidate, a television political leader, is able to impact on an audience that is larger than the one exposed to the propagandistic tools, and they can obtain an advantageous position in the distribution of votes.